The cost of consumer payments in Sweden - Björn Segendorf; Thomas Jansson (Sveriges Riksbank, 2012)
We estimate the social and private costs of consumer-to-business payments in Sweden in 2009. The combined social cost for these payments was 0.68 per cent of GDP. At the point of sale, cash is socially less costly than debit cards for payments below EUR 1.88 (SEK 20) and credit cards below EUR 42.37 (SEK 450). The corresponding thresholds for the individual consumer are higher for debit cards and much lower for credit cards. Using unique survey data we show that consumers' payment behaviour is not consistent with what is socially optimal.
Keywords: D12; D23; D24; 330; Cash payments; Card payments; Credit transfers; Direct debits; Social costs; Private costs; Zahlungsverkehr; Bargeldloser Zahlungsverkehr; Kredittilgung; Soziale Kosten; Schweden